The second stage of labour - Singh, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The second stage of labor begins with full dilatation of cervix and ends with delivery of the fetus. In most of the cases the labor progresses uneventfully, without any need of an active intervention but in few cases complications may occur. With passage of time there has been better understanding about second stage of labor, still there are several grey areas yet to be resolved. This review endeavours to scrutinize a variety of care practices including positions, time and type of pushing, use of epidural analgesia, and perineal support techniques etc and discuss evidence based management of second stage of labor. The review was carried out in the period of 1900-2019 by searching in Pub Med, Embase, Scopus, Google scholar, Web of sciences using relevant key words. Reports, articles, fact sheets and official publications of World health Organization (WHO), Ministry of health and family welfare-Govt of India and various other countries were also reviewed.